Analysis of Optimal Portfolio Formation Using a Single Index Model as a Basis for Investment Decision Making [Study on the Jakarta Islamic Index (JII) 2015-2017] - Ayun Niyawati; Wisnu Panggah Setiyono (International Consortium of Education and Culture Research Studies, 2021)
The aim of this research is to know the performance ofstocks that become the member ofJakarta Islamic Index (JII) and determine what stocks are part of the optimal portfolio. This research is a quantitative descriptive study. The technique of taking samples is using purpose sampling techniques, with determined criteria. The population needed in this study is 42 stocks. After doing the sampling purposes, the sample is 20 stocks. The analysis technique used is the Single Index Model. The results of this study reveal that there are 5 stocks which eligible to become optimal portfolio members. These shares are UNTR, AKRA, UNVR, TLKM, and ADRO. Then the proportion offunds in each consecutive share is 31.58%, 15.18%, 28.02%, 17.7% and 7.52%. While the portfolio of the portfolio formed (expected portfolio return) is 0. 0203 or 2. 03% with portfolio risk of0. 0006 or 0. 06%.